Mechanical Properties and Constitutive Model of Selective Laser Melting 316L Stainless Steel at Different Scanning Speeds - Yongling Li; Yongsheng Ge; Jingfa Lei; Wei Bai (Advances in Materials Science and Engineering)
To investigate the effects of different scanning speeds on the mechanical properties of selective laser melting 316L stainless steel (SLM 316L SS), process specimens with scanning speeds at 350 mm/s, 650 mm/s, 950 mm/s, and 1250 mm/s were prepared using the SLM technique in this paper. The quasistatic and dynamic compressive mechanical properties of the four specimens were tested by electrohydraulic servo experimental machine and Hopkinson compression bar experimental device, and the mechanical differences of the specimens were analyzed by microscopic observation. Finally, the modified Johnson-Cook (J-C) model was adopted to describe the dynamic mechanical properties of SLM 316L SS. Results showed that the four process steel specimens exhibited typical viscoplastic characteristics and significant strain rate strengthening effects in the mechanical property tests. Moreover, the scanning speed significantly affects the internal defects and melt pool characteristics of the SLM 316L specimens, and the yield strength decreases significantly with the disappearance of the melt pool characteristics. Finally, the modified J-C model can better describe the mechanical behavior of SLM 316L SS material more accurately. This study can provide theoretical references for improving the fabrication process of SLM 316L SS to broaden the practical application of this material.